The clinical effectiveness and safety of low/moderate-intensity statins & ezetimibe combination therapy vs. high-intensity statin monotherapy: a systematic review and meta-analysis - Pishoy Sydhom; Bakr Al-Quraishi; Mohamad El-Shawaf; Mohamed T. Osman; Nourhan Naji; Nouran Awwad; Nahla Shehata; Mostafa Osama; Heba Sergany; Kerollos F. Maurice; Ahmed Sayed (BMC Cardiovascular Disorders)
Abstract Background Despite widespread use of high-intensity statin monotherapy, achieving target LDL-C levels and reducing cardiovascular events in patients with or at high risk of developing ASCVD remains challenging. Our study measured the effects of low/moderate-intensity statins and ezetimibe combination therapy compared to high-dose statin monotherapy on major adverse cardiovascular events (MACEs) and coronary atherosclerotic plaque reduction. Methods We searched PubMed, Scopus, Web of Science, and Cochrane CENTRAL register of trials for studies comparing the combination therapy to high-intensity statin monotherapy in terms of MACEs and coronary atherosclerotic plaque reduction. The primary outcome was a composite of cardiovascular death or major cardiovascular events (MI, HF, Revascularization, or non-fatal stroke). Other outcomes included other MACEs, lipid-lowering efficacy, and safety outcomes. A protocol was registered to PROSPERO under registration number [CRD42024545807]. Results 15 studies encompassing 251,450 participants were included in our meta-analysis. In our pooled analysis of observational studies, combination therapy was associated with lower rates of the primary composite outcome (HR = 0.76, CI 95% [0.73, 0.80]), cardiovascular death (HR = 0.80, CI 95% [0.74, 0.88]), all-cause death (HR = 0.84, CI 95% [0.78, 0.91]), and non-fatal stroke (HR = 0.81, CI 95% [0.75, 0.87]). However, the pooled analysis of RCTs did not demonstrate a statistically significant difference between both arms concerning clinical endpoints. Combination therapy had a higher number of patients with LDL-C < 70 mg/dL (RR = 1.27, CI 95% [1.21, 1.34]), significantly lowered LDL-C (MD = -7.95, CI 95% [-10.02, -5.89]) and TC (MD = -26.77, CI 95% [-27.64, -25.89]) in the pooled analysis of RCTs. In terms of safety, the combination therapy lowered muscle-related adverse events (RR = 0.52, CI 95% [0.32, 0.85]) and number of patients with liver enzyme elevation (RR = 0.51, CI 95% [0.29, 0.89]) in the pooled analysis of RCTs and was associated with lower rates of new-onset diabetes (HR = 0.80, CI 95% [0.74, 0.87]) in the pooled analysis of observational studies. Conclusion Evidence from RCTs indicates that low/moderate statin therapy in combination with ezetimibe has a superior lipid-lowering effect and reduces side effects compared to high-dose statins. Observational studies suggest improved clinical outcomes but need to be corroborated by large, outcomes-powered RCTs over longer follow-up periods.